The incidence of injuries and illness during open-water swimming events: optimising swimmer safety - Alifrangis, A.; Suzan, M.; Kipps, C. (British Journal of Sports Medicine, 2021)
Background: Open-water swimming (OWS) is a popular massparticipation sport in the UK; however, it presents unique safety and medical challenges. Objective: To compare the incidence of illness and injury during OWS events with those in the swim leg of similar distance triathlon events. Design: Retrospective analysis of OWS and triathlon water rescue race reports. Setting: Mass-participation community-based OWS races (between 200m and 1900m distance) and triathlons (400m, 750m and 1500m swim leg) in the UK between 2013-2016. Patients (or Participants) All participants requiring intervention from the water rescue team were included. Relay participants were excluded. Interventions (or Assessment of Risk Factors): Event type, swimming distance, and participant demographics were recorded. Main Outcome Measurements: Reasons for intervention and/or extraction from the water by the rescue teams were logged. Results: Reports from 4 OWS races and 7 triathlons were analysed. There were 60,859 participants in total. 490 swimmers required intervention from the water rescue team in the OWS races, of which 50/490 (11%) required extraction (3/1000 swimmers). In triathlon events, 818 required intervention during the swim leg, and 232/818 (28%) required extraction (5/ 1000 participants). Reasons cited for extractions in both groups were tiredness (approximately one third) and breathing difficulties (18% OWS extractions, 15% triathlon extractions). Cramp was more common in the OWS group (31% vs 12% in the triathlon group), whereas injury was more likely to be a cause for extraction in the triathlon (8% vs 1.4% in OWS). In the triathlon there were two cases of cardiac arrest in the water. Conclusions: Open-water swimming has a low incidence of illness and injury, but in some cases can result in serious medical illness and death. This study gives an insight into the common causes for intervention from the water rescue teams. Event organisers and medical teams should be aware of the risks to ensure optimal medical care and competitor safety for all open-water swimming and triathlon events.